Microbial lipid production by oleaginous yeast Cryptococcus sp. in the batch cultures using corncob hydrolysate as carbon source. (January 2015) - Chang, Yi-Huang; Chang, Ku-Shang; Lee, Ching-Fu; Hsu, Chuan-Liang; Huang, Cheng-Wei; Jang, Hung-Der
Abstract: To realize the feasibility of biodiesel production from high-lipid cell culture, microbial lipid production by the oleaginous yeasts was studied using glucose and sucrose as carbon source. Among the tested strains, Cryptococcus sp. SM5S05 accumulated the highest levels of intracellular lipids. The crude lipid contents of Cryptococcus sp. cultured in yeast malt agar reached 30% on a dry weight basis. The accumulation of lipids strongly depended on carbon/nitrogen ratio and nitrogen concentration. The highest content of lipids, measured at a carbon/nitrogen ratio of 60–90 and at a nitrogen concentration of 0.2%, was 60–57% lipids in the dry biomass. Batch cultures using corncob hydrolysate demonstrated that there was minimal inhibitory effect with a reducing sugar concentration of 60 g l −1 or higher. Batch cultures of Cryptococcus sp. SM5S05 in the corncob hydrolysate medium with 60 g l −1 glucose resulted in a dry biomass, lipid yields, and content of 12.6 g l −1, 7.6 g l −1, and 60.2%, respectively. The lipids contained mainly long-chain saturated and unsaturated fatty acids with 16 and 18 carbon atoms. The fatty acid profile of Cryptococcus oils was quite similar to that of conventional vegetable oil. The cost of lipid production could be further reduced with corncob hydrolysate being utilized as the raw material for the oleaginous yeast. The results showed that the microbial lipid from Cryptococcus sp. was a potential alternative resource for biodiesel production. Highlights: Microbial oil production from oleaginous yeast Cryptococcus sp. was studied. Accumulation of lipid strongly depended on C/N ratio and nitrogen concentration. Cultures in hydrolysate medium with 60 g/l glucose resulted in maximum lipid yields. Maximal lipid content in the Cryptococcus sp. were 60.2% on dried weight basis.